Implementasi Aplikasi Kasir Pada Warung Chicken Geprek Sahabat Berbasis Desktop Menggunakan Vb.Net - Candra Naya; Bayu Nugroho; Elkin Rilvani (Teknik Informatika, Universitas Pelita Bangsa, 2022)
Abstract Warung Chicken Geprek Sahabat is one of the businesses engaged in the sale of ready-to-eat chicken geprek, in the process of selling the system it is still done manually and the reports generated are only stored in the form of documents as archives, resulting in loss of documents and accumulation of papers resulting in excessive use of paper. Therefore, to make it easier for the friend's chicken geprek stall, the researcher made data processing and transaction reports, the researcher took advantage of the use of technology, one of which was computer technology by making a cashier application for the friend's chicken geprek stall. The purpose of this cashier application design is to assist the stall's activities in processing data such as food and beverage data, user data, sales transaction data, as well as daily and monthly transaction reports. The process of designing this cashier application uses Microsoft Visual Basic as the programming language used, as well as application development using the waterfall method. The result of this research is a desktop-based friend's chicken geprek cashier application program with vb.net which can make it easier for administrators and employees to process chicken geprek friends data. Keywords: Program, Cashier Application, Microsoft Visual Basic, Sales